2010
DOI: 10.2174/138161210790112728
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics in Psychiatry - A Useful Clinical Tool or Wishful Thinking for the Future?

Abstract: More than fifty years of pharmacogenetic research have produced many examples of the impact of inherited variability in the response to psychotropic drugs. These successes, however, have as yet failed to translate into broadly applicable strategies for the improvement of individual drug treatment in psychiatry. One important argument against the widespread adoption of pharmacogenetics as a clinical tool is the lack of evidence showing its impact on medical decision making and on risk benefit ratio for the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 90 publications
(98 reference statements)
1
22
0
1
Order By: Relevance
“…Genetic variants of these enzymes result in large individual differences in clearance, half-life, and peak blood concentration that ultimately influence individual drug response and toxicity. For example, the number of functional CYP2D6 alleles will result in a fast metabolizer (2 alleles) or poor (0 alleles) phenotype [34,35]. Genetic tests are available to determine the variants in individual patients and the US FDA recommends their use to better individualize treatment for many classes of drugs, including the antidepressants.…”
Section: Treatment Of Mddmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic variants of these enzymes result in large individual differences in clearance, half-life, and peak blood concentration that ultimately influence individual drug response and toxicity. For example, the number of functional CYP2D6 alleles will result in a fast metabolizer (2 alleles) or poor (0 alleles) phenotype [34,35]. Genetic tests are available to determine the variants in individual patients and the US FDA recommends their use to better individualize treatment for many classes of drugs, including the antidepressants.…”
Section: Treatment Of Mddmentioning
confidence: 99%
“…Many, including health-insurance companies and health care providers, still need to be persuaded that personalization in drug selection provides enough benefits to justify the cost. Further genotyping may have more clinical importance in diseases like MDD, where there are high rates of non-responders, as all methods providing information on individual drug response can be of clinical significance [34,37,38].…”
Section: Contribution Of Pharmacogenetics and Metabolism To Therapeuticmentioning
confidence: 99%
“…However, results from studies on the contribution of genetics to therapeutic outcome have often been found to be non-reproducible, or data from prospective studies are lacking, as exemplified in the field of psychiatry. Antidepressant and antipsychotic drugs are widely subject to TDM since there is a large interindividual variability in plasma concentrations, partly due to the strong effect of the patient's genetic background based on individually different metabolic rates of cytochrome P4502D6 [14]. It was therefore anticipated that CYP2D6 would have severe consequences on the side effects and clinical outcomes of patients being treated without consideration of the metabolizer status.…”
Section: Uncertain Role Of Pharmacogenetics In Personalized Medicinementioning
confidence: 99%
“…The clearance of most tricyclics evidently depend on CYP2D6 polymorphisms, and some studies have shown an overrepresentation of CYP2D6 poor metabolizers among patients reporting adverse events [16,29] or of ultra-rapid metabolizers in cases in which the drug therapy has been ineffective [29,31]. The kinetics has not yet been translated into clinical practice, and concern has been expressed as to whether any genotype-related adjustment of dosage can improve the clinical outcome in terms of clear psychometric measures or if relevant adverse events can be prevented [14]. There have been large retrospective trials on the susceptibility of depression and outcome measures, also in relation to genetic variants in the serotoninergic system [28]; however, no genetic trait has been accepted as yet as a useful predictor of the therapeutic outcome in daily practice.…”
Section: Uncertain Role Of Pharmacogenetics In Personalized Medicinementioning
confidence: 99%
“…The hope is that, by indexing symptomatic improvement in terms of changes in the function of neural circuits, one may be able to characterise the modes of operation of different psychotherapy approaches and their impact on the processes involved in cognition and emotion (Roffman et al 2005). In this respect, the role of neuroimaging is similar to the one envisaged in other settings where the observed behaviour, traits, or the inferred mental states of an individual appear to be too general to be effectively associated with the variable of interest (Gottesmann and Gould 2003), as in genetics (Meyer-Lindenberg and Weinberger 2006), in the identification of markers for individually targeted pharmacotherapy (Kirchheiner et al 2010), or in psychiatric diagnosis (Insel et al 2010). In all these fields of application, the rationale for the adoption of neuroimaging techniques is a more specific characterisation of differences in mind functioning than the one obtainable by observing behavioural variables.…”
Section: Introductionmentioning
confidence: 99%